2002
DOI: 10.1099/0022-1317-83-12-3123
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation and immunohistochemical differences among geographic isolates of Taura syndrome virus of penaeid shrimp

Abstract: Taura syndrome virus (TSV) is an important virusTaura syndrome virus (TSV) is one of the most economically significant viruses infecting penaeid shrimp in the western hemisphere Brock et al., 1995). Penaeus vannamei, P. schmitti and P. setiferus are the most susceptible species, whereas P. stylirostris, P. monodon, P. japonicus, P. duorarum, P. chinensis and P. aztecus are considered TSV tolerant (Brock, 1997 ;Overstreet et al., 1997). TSV infection in P. vannamei, the principal host of the virus, consists of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 23 publications
2
29
0
Order By: Relevance
“…The introduction of P. vannamei culture in Taiwan, China, Thailand and Indonesia also resulted in the spread of TS virus (TSV) to these regions within a relatively short period of time (Tu et al 1999, Yu & Song 2000, Nielsen et al 2005. Several genotypes or strains are now known to exist and the virus remains an important infectious disease in countries where P. vannamei is farmed (Erickson et al 2002, Lien et al 2002, Robles-Sikisaka et al 2002, Rosenberry 2002.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of P. vannamei culture in Taiwan, China, Thailand and Indonesia also resulted in the spread of TS virus (TSV) to these regions within a relatively short period of time (Tu et al 1999, Yu & Song 2000, Nielsen et al 2005. Several genotypes or strains are now known to exist and the virus remains an important infectious disease in countries where P. vannamei is farmed (Erickson et al 2002, Lien et al 2002, Robles-Sikisaka et al 2002, Rosenberry 2002.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, all of the MAb reacted with multiple antigen bands in gels prepared from purified TSV (Poulos et al 1999). Application of one of the MAb (designated 1A1 and specific to VP1) for immunohistochemical detection of TSV infection in shrimp gave positive results with TSV isolates from Taiwan, USA and Hawaii, but negative results for TSV isolates from Mexico, Nicaragua and Belize (Robles-Sikisaka et al 2002, Erickson et al 2005. Phylogenetic analysis of the TSV capsid protein 2 gene (also called CP2 but equivalent to VP1) from various sources revealed 3 distinct geographic groups associated with Belize, the USA and Southeast Asia (Tang & Lightner 2005).…”
Section: Specificity Of Mabmentioning
confidence: 99%
“…MAb specific to VP1 (designated 1A1) was used to develop Western-blot, dot-blot and immunohistochemical assays for detection of various TSV strains. However, this MAb failed to detect several isolates of TSV from various sources (Erickson et al 2002, Robles-Sikisaka et al 2002. Polyclonal antibodies against recombinant proteins of VP1 and VP3 have also been developed (Chaivisuthangkura et al 2006).…”
Section: Abstract: Penaeus Vannamei · Monoclonal Antibody · Mab · Tamentioning
confidence: 99%
“…ORF1 and ORF2 are predicted to encode the nonstructural and structural polyproteins, respectively. Phylogenic analysis based on the nucleotide sequences of CP2 suggested that there are 3 lineages, namely the Americas, Belize, and SE Asia, among the various geographic TSV isolates (Robles-Sikisaka et al 2002, Tang & Lightner 2005. In the CP1 and CP2 regions, low genetic variation (0 to 0.24% for CP1 and 0 to 0.35 or 0 to 5.6% for CP2 nucleotide sequences) was observed among the isolates analyzed.…”
Section: Introductionmentioning
confidence: 95%
“…TSV disease has spread widely via infected broodstock throughout America and Southeast Asia, causing severe economic losses in the shrimp aquaculture industry in the last decade (Brock 1997, Tu et al 1999, Robles-Sikisaka et al 2002, Chang et al 2004. TSV is known to cause high mortality in P. vannamei, P. schmitti, and P. seiferus, while sparing P. stylirostris, P. monodon, P. japanicus, P. duorarum, P. chinensis, and P. aztecus (Brock 1997, Overstreet et al 1997.…”
Section: Introductionmentioning
confidence: 99%